Open-source security operations center (SOC) : a complete guide to establishing, managing, and maintaining a modern SOC - Basta, Alfred; Basta, Nadine; Anwar, Waqar; Essar, Mohammad Ilyas (2025)
"The Security Operation Center (SOC) is a centralized function within an organization that uses people, procedures, and technology to prevent, identify, analyze, and respond to cybersecurity incidents while continuously monitoring and improving an organization's security posture. The emergence of sophisticated threats placed a premium on gathering context from several sources. An SOC is a central command post collecting telemetry from across an organization's IT infrastructure, including networks, devices, appliances, and data stores, regardless of where such assets are located. Essentially, the SOC is the point of contact for any events logged within the organization that is being monitored. The SOC must decide how each event will be managed and handled"--
Keywords: Cyberinfrastructure -- Security measures; Computer networks -- Security measures; Cyberterrorism -- Prevention